ISU DISKRIMINASI HUKUM HAK ASASI MANUSIA KEPADA WARIA (KAJIAN STRATEGI KOMUNIKASI TERKAIT PERLINDUNGAN WARIA DI INDONESIA) - Monica Bulan Yudiciana Sinaga; Wa Ode Seprina (Universitas Bunda Mulia, 2013)
Republic of Indonesia is one of the biggest countries in the world. It hasapproximately 238 million inhabitants among over 17.500 islands in different culture, language, lifestyle, etc. All the difference has become unique as it is all covered by national motto which is called Bhineka Tunggal Ika. With all the differences, it comes discriminations in various backgrounds such as discrimination against race, ethnic, age, gender, social economic, etc. Discrimination has become an issue in Indonesia and one of the cruelest discriminations that have happened in the country. Discrimination against transvestites has become an issue since a long time a go in Indonesia. This issue is still happening around us in Indonesia although there is a law to fight against the issue. As what Crable and Vibbert said “an issue is created when one or more human agents attaches significance to a situation or perceived problem” (Gaunt, 1995). TheIndonesian Ministry of Justice and Human Rights is a government institution which is specialized in liability of protection and human rights for Indonesians. It is their responsible to protect all Indonesian citizen no matter who they are, what their social background are and etc. The Ministry have to inform Indonesians that transvestites deserve to be treated likeother Indonesian citizen and there is no discrimination on the implementation of policy for transvestites. All they need is a proper communication.Keywords: Comunication Strategy, Discrimination, Shemale, Human Right